Impact Of Short Selling In Financial Markets - Sharma, Neha (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
With the financial crisis gripping the stock market worldwide in the last few months of 2008, there have been widespread criticisms on the process of short selling. The opponents have questioned the existence of short selling and argued about the foul play of the short selling. Following such widespread campaigning, in order to boost the investors confidence short selling was either or restricted in most of the Western markets and in the Anglo-Saxon countries. Nevertheless, the financial experts and economists were divided in the opinion of anning short selling. Many argued that such ban will affect the market efficiency and disturb the market from operating freely and fairly. Hence the current research is about the impacts or the effects the ban on short selling have on the financial markets, especially the capital markets. This study focuses on finding such effects in a neutralised approach and free from bias to any side. The research is compiled in such a way that, the literature review was conducted with an aim of uncovering the loop holes and functioning of short selling experts. Accordingly, the findings of the literature review are in the form of a list of key characteristics short selling possess which increases the efficiency of the system. These key characteristics are evaluated based on the stock price variations in the LSE. The conclusions are drawn based on the findings on the literature review and the analysis done on the stock price movements, crude oil price variation and a survey on the perception of short selling. Based on the findings, a set of commendations are made which will help in the further understanding of the short selling.